Characteristics and Photocatalytic Performance of Coprecipitation Praseodymium (Pr)-doped Strontium Titanate for Methylene Blue Degradation - Salsa Nurul Khoiria; Dianisa Khoirum Sandi; Fahru Nurosyid; Risa Suryana; Yofentina Iriani (BRIN Publishing (Penerbit BRIN), 2026)
Strontium titanate (SrTiO₃ or STO) is a perovskite material with promising photocatalytic properties for wastewater degradation. Doping with rare-earth elements such as praseodymium (Pr) can enhance its performance by modifying structural and electronic characteristics. In this study, Pr-doped STO (Sr1-xPrxTiO3, x = 0%, 2%, and 4%) was synthesized via the coprecipitation method. X-ray diffraction (XRD) confirmed a single-phase perovskite structure with high crystallinity, while Fourier transform infra-red (FTIR) analysis verified the formation of Sr–Ti–O bonds. Particle size analysis (PSA) and surface area analysis (SAA) with the Brunauer-Emmett-Teller (BET) method revealed that higher Pr concentrations reduced particle size and increased surface area. Photocatalytic activity was evaluated using methylene blue (MB) degradation under ultraviolet (UV) irradiation for up to 5 hours. The Sr0.98Pr0.02TiO3 sample exhibited the best performance, achieving 73.08% MB degradation after 5 hours, demonstrating the effectiveness of moderate Pr doping in enhancing photocatalytic activity